HUMAN RESOURCE DEVELOPMENT ANALYSIS, WORK ETHIC, AND WORK ENVIRONMENT IN IMPROVE EMPLOYEE PERFORMANCE AT PT SUPRA JAYA ABADI MEDAN - Nuraini Kemalasari Istiqamah; Akhmad Taufik; Putria Habibah (Yayasan Multidimensi Kreatif, 2025)
The research analysis aims to analyze the development of Human Resources, Work Ethic, and Work Environment in Improving Employee Performance at PT Supra Jaya Abadi. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This study used multiple linear regression analysis. The sample in this study was 75 respondents. Primary data collection was done using a questionnaire. The results of the study show that the test results for the HR development variable show a calculated t-value of 7.370 > ttable of 1.99 with a significant value of 0.000 < 0.05, then the H1 hypothesis is accepted and H0 is rejected, meaning that human resource development has a positive and partially significant effect on employee performance. The test results for the work ethic variable showed a calculated t-value of 6.306> ttable of 1.99 with a significant value of 0.000 < 0.05, then the H2 hypothesis was accepted and H0 was rejected, meaning that work ethic had a positive and partially significant effect on employee performance. The test results for the work environment variable showed a calculated t-value of 3.657 > ttable of 1.99 with a significant value of 0.006 < 0.05, then the H3 hypothesis was accepted and H0 was rejected, meaning that the work environment had a positive and partially significant effect on employee performance. The result of F calculation is 44.431 which is greater than 2.73 and the significant value of 0.000 is less than 0.05 so that it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected so that it can be concluded that human resource development, work ethic and work environment have a significant effect simultaneously on employee performance.